Systemic kanamycin treatment has no effect on cell numbers in the mouse utricular macula - Kirkegaard, Mette (Image analysis and stereology, 2005)
The aim of the present study is to estimate the total number of the sensory hair cells (chalice innervated and bouton innervated) and supporting cells in the mouse utricular sensory epithelium at two different time points after systemic kanamycin treatment. Mice were given two daily subcutaneous injections of kanamycin (600 or 900 mg/kg) for 15 consecutive days and allowedto survive either 1 or 3 weeks after end of treatment. Cell numbers were estimated using a physical fractionator. Paraffin-embedded tissue was immunohistochemically stained for active caspase-3 in order to detect apoptosis. There was no change in hair cell or supporting cell number after treatment with kanamycin and the survival time had no effect. Although no positive staining for caspase-3 was seen, hair cells with swollen chalices anddark stained nuclei were observed in the sensory epithelium of the treated animals, indicating some effect of the treatment. In conclusion, the dosing regime and survival times studied here are not sufficient to induce hair cell loss in the mouse utricle.
Keywords: Dlakaste celice notranje; Saccule And Utricle; Drug Effects; Kanamicin; Cytology; Sakula in utrikula; Kanamycin; Celica, štetje; Hair Cells, Inner; Imunohistokemija; Miši seva BALB C; Mice, Inbred Balb C; Immunohistochemistry; Slika, obdelava z računalnikom; aminoglikozidi; Cell Count; celice; Image Processing, Computer-Assisted; dlake; epitelij; stereologija; miši